The Drosophila gene morula inhibits mitotic functions in the endo cell cycle and the mitotic cell cycle. - Reed, B.H.; Orr-Weaver, T.L. (Development, 1997)
In the endo cell cycle, rounds of DNA replication occur in the absence of mitosis, giving rise to polyploid or polytene cells. We show that the Drosophila morula gene is essential to maintain the absence of mitosis during the endo cycle. During oogenesis in wild-type Drosophila, nurse cells become polyploid and do not contain cyclin B protein. Nurse cells in female-sterile alleles of morula begin to become polyploid but revert to a mitotic-like state, condensing the chromosomes and forming spindles. In strong, larval lethal alleles of morula, the polytene ring gland cells also inappropriately regress into mitosis and form spindles. In addition to its role in the endo cycle, morula function is necessary for dividing cells to exit mitosis. Embryonic S-M cycles and the archetypal (G1-S-G2-M) cell cycle are both arrested in metaphase in different morula mutants. These phenotypes suggest that morula acts to block mitosis-promoting activity in both the endo cycle and at the metaphase/anaphase transition of the mitotic cycle. Consistent with this, we found cyclin B protein to be inappropriately present in morula mutant nurse cells. Thus morula serves a dual function as a cell cycle regulator that promotes exit from mitosis and maintains the absence of mitosis during the endo cycle, possibly by activating the cyclin destruction machinery.